Identifying pulmonary embolism - high risk patients after total knee replacement: systematic review - Jannatin Nisa Arnindita,; Muhammad Hanun Mahyuddin,; Pandit Bagus Tri Saputra,; Rendra Mahardhika Putra, (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the incidence, onset, risk factors and mortality of pulmonary embolism in total knee replacement patients. Method: The systematic review was conducted in September 2022, and comprised search on PubMed, ScienceDirect, Scopus and Crossref databases for studies published from 1977 till September 7, 2022, in the English language related to the incidence of pulmonary embolism after primary total knee replacement. Cochrane Handbook for Systematic Reviews of Interventions was used to assess risk of bias, and the Newcastle-Ottawa Scale was used to assess the quality of evidence. Results: Of the 3,910 studies initially identified, 66(1.68%) were analysed in detail, which together had 13,258,455 total knee replacement patients. Pulmonary embolism was reported in 76,515(0.58%) cases. The onset of pulmonary embolism ranged 2-150 days post-surgery. Patients with older age, diabetes mellitus, higher body mass index, atrial fibrillation, previous venous thromboembolism, high Charlson Comorbidity Index score, hypertension, arrhythmia and chronic heart failure were at significantly higher risk (p<0.05). The overall mortality rate of pulmonary embolism in such cases ranged 10.53-100%. Conclusion: Pulmonary embolism is a rare complication after orthopaedic surgery, but it has a very high mortality rate. By recognising the risk factors, attending physicians can optimise the use of chemoprophylaxis, thus preventing pulmonary embolism. Key Words: Venous thromboembolism, Orthopaedic, Pulmonary, Arrhythmias, Cardiac, Bibliometrics, Comorbidity.